Development of ZnO/AlFeO3 composite via hydrothermal method as supercapacitor electrode - Ahmad, Tamoor; Alotaibi, B. M.; Alrowaily, Albandari. W.; Alyousef, Haifa A.; Dahshan, A.; Henaish, A. M. A.; Ahmad, Khursheed (Journal of sol-gel science and technology, 2024)
The conversion and preservation of energy have been the subject of extensive research because of the increasing need for renewable and pollution-free energy sources. With an extended lifespan, excellent charge-discharge properties, and substantial power density, electrochemical supercapacitors are a special class of potential energy storage systems that find use in various processes. Much effort has been put into improving the electrode material’s composition to boost supercapacitors’ performance. In this work, hydrothermally generated ZnO/AlFeO 3 composite was analyzed by several physical and chemical characterizations to be an effective and high-performing electrode material. According to evaluated data, the ZnO/AlFeO 3 composite exhibited a pure crystalline phase, increased surface area, and heightened electrochemical efficiency showing a specific capacitance of 1232 F/g at 1 A/g with 52 Wh/kg of specific energy and 276 W/kg of specific power along with favorable CV stability after 5000th cycles. Better electrical characteristics were displayed by the ZnO/AlFeO 3 composite, as evidenced by the composite’s reduced solution resistance and lower charge transfer resistance in the impedance outcomes. The ZnO/AlFeO 3 composite demonstrated extraordinary efficiency by displaying enhanced ion mobility, better electrical conductivity, and a quick charge-storing technique, indicating the potential of the ZnO/AlFeO 3 composite for the upcoming era of power storage. Graphical Abstract Highlights Hydrothermally developed ZnO/AlFeO 3 composite was utilized as a supercapacitor electrode. Composite demonstrated remarkable physical features assessed via various physical characterizations. An enriched specific capacitance of 1232 F/g at 1 A/g was observed through the GCD results. EIS results depicted the improvement in resistive properties of ZnO/AlFeO 3 composite.